2012
DOI: 10.1016/j.ecolecon.2012.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Provision of environmental output within a multi-output distance function approach

Abstract: This paper rede nes technical e ciency by incorporating provision of environmental goods as one of the outputs of the farm within a multi-outptut distance function framework.Permanent and rough grassland area are used as a proxy for the provision of environmental goods. The multi-output distance function approach is used to estimate technical e ciency.A Bayesian procedure involving the use of a Gibbs sampler is used to estimate the farm speci c e ciency as well as the coe cients of the distance function. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Areal et al [74] argue that if the information received by policy makers concerning farm efficiency levels is harmonized with policy aims, policy measures may be targeted to support the targeted farms. This deserves further consideration given that the literature that links efficiency and climate change adaptation is limited.…”
Section: Efficiency and Climate Change Adaptationmentioning
confidence: 99%
“…Areal et al [74] argue that if the information received by policy makers concerning farm efficiency levels is harmonized with policy aims, policy measures may be targeted to support the targeted farms. This deserves further consideration given that the literature that links efficiency and climate change adaptation is limited.…”
Section: Efficiency and Climate Change Adaptationmentioning
confidence: 99%
“…Feng and Serletis [18] studied the total factor productivity of the large US Banks (assets at more than $one hundred million) from 2000 to 2005, and found that the average annual growth rate of these banks' total factor productivity during this period is 1.98%, but the total factor productivity growth rate showed a trend of decline, this is mainly due to a slowdown in the technical improvement. Areal et al [19] tor, and denied the "pollution haven hypothesis". Wang et al [28] analyzed the energy efficiency and productivity of 28 provinces in China (excluding Hainan and Tibet) in the "eleventh five-year plan" by using the directional distance function, and compared three situations: energy conservation; energy conservation and emission reduction; energy conservation, emissions reduction and economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, there are many studies that evaluate the effect of different methodologies and study-specific characteristics on TE Haghiri, et al, 2004;Areal, et al, 2012;Van Der Voort, et al, 2014). Some authors defend the two-stage procedure (Banker & Natarajan, 2008;McDonald, 2009) and other authors Battese & Coelli, 1995) criticise this approach by arguing that "the factors should be incorporated directly in the estimation of the production frontier because such factors may have a direct impact on efficiency" (Sharma, et al, 1999, p. 26).…”
Section: Non-parametric and Parametric Modelsmentioning
confidence: 99%
“…Geographical location Álvarez & González, 1999) and farm size Areal, et al, 2012) are other factors that can affect the TE and despite the lack of general agreement, one might hypothesize that dairy farms with high levels of TE tend to be higher in a favourable context. Although the choice of the methodology to measure TE can have a direct impact on the results, there is no agreement as to the most appropriate methodology for a given situation (Olesen, et al, 1996), which remains a matter of ongoing debate .…”
Section: Understanding the Factors Affecting Technical Efficiency (Tementioning
confidence: 99%
See 1 more Smart Citation